Endoscopic ultrasonography‐guided pancreatic duct drainage after failed endoscopic retrograde cholangiopancreatography in patients with malignant and benign pancreatic duct obstructions. (25th April 2013) - Kurihara, Toshio; Itoi, Takao; Sofuni, Atsushi; Itokawa, Fumihide; Moriyasu, Fuminori
Abstract : Background: Endoscopic ultrasonography (EUS)‐guided pancreatic drainage has been advocated as a rescue treatment for management of patients in whom retrograde access to the pancreatic duct (PD) is technically unsuccessful. The aim of the present study was to evaluate the feasibility and efficacy of EUS‐guided drainage for failed endoscopic retrograde cholangiopancreatography. Patients and Methods: A total of 17 EUS‐guided PD drainage (EUS‐PD) procedures were carried out in 14 patients (age: mean 64.6 years, range 54–81 years, eight men). Results: The rendezvous technique was successful in 11 of 17 procedures (64.7%). Three of five patients with an unsuccessful rendezvous technique successfully underwent EUS‐PD stenting (7‐Fr plastic stent [two cases], 5‐Fr endoscopic nasobiliarydrainage [one case]). In the two remaining patients, puncture and pancreatography were successful; however, antegrade passage of the guidewire failed. Conclusion: EUS‐guided decompression of PD is a feasible and effective treatment for the management of symptomatic high‐pressure PD due to stricture of the PD and/or stenotic pancreatodigestive anastomosis. However, this procedure is technically challenging, has a high rate of complications, and should be done only at tertiary‐care centers.